Seismic fragility analyses of sea-crossing cable-stayed bridges subjected to multi-support ground motions on offshore sites. (15th June 2018) - Li, Chao; Li, Hong-Nan; Hao, Hong; Bi, Kaiming; Chen, Baokui
Highlights: Seismic fragilities of sea-crossing cable-stayed bridges are numerically analyzed. Multi-support ground motions at different depths of offshore sites are simulated. Effects of SSI and hydrodynamic added mass are systematically investigated. Abstract: As key components in the transportation networks at coastal areas, sea-crossing cable-stayed bridges play a very important role in the development of regional economy. These bridges may be subjected to severe earthquakes during their life-cycles. Owing to the lack of actual seafloor earthquake recordings and approaches in synthesizing offshore seismic motions, the onshore seismic motions are commonly utilized as inputs in the seismic design of sea-crossing cable-stayed bridges. However, this approach may lead to erroneous structural response predictions since the characteristics of onshore and offshore seismic motions are different. In this paper, the seismic performance of a sea-crossing cable-stayed bridge is comprehensively evaluated based on the fragility function methodology. A novel approach is presented to theoretically calculate the ground motion transfer function at any location within an offshore site and stochastically synthesize the offshore multi-support ground motions at different depths (MGMDDs). The OpenSees analysis platform is employed to develop the three-dimensional finite element model of the example bridge, in which the p-y, t-z and q-z elements are installed at the pile nodes to simulate the interaction between the bridge piles and surrounding soils. Moreover, the effect of seawater on the bridge seismic responses is modeled using the hydrodynamic added mass method. The seismic fragility curves of the example bridge are generated by using the synthesized MGMDDs as inputs. The influences of spatial and depth varying offshore seismic motions, soil-structure interaction (SSI) and seawater added mass on the bridge component and system fragilities are investigated and discussed. Numerical results show that the seismic fragility of the example sea-crossing cable-stayed bridge is affected by the above mentioned influencing factors with different extents. The proposed approach can rationally and effectively assess the seismic fragilities of sea-crossing cable-stayed bridges.